2021
DOI: 10.1021/acsami.1c18902
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of CO2 to HCOOH over Copper Catalysts

Abstract: Although great progress has been made in the field of electrochemical CO2 reduction reaction (eCO2RR), inducing product selectivity is still difficult. We herein report that a thiocyanate ion (SCN–) switched the product selectivity of copper catalysts for eCO2RR in an H-cell. A cuprous thiocyanate-derived Cu catalyst was found to exhibit excellent HCOOH selectivity (faradaic efficiency = 70–88%) over a wide potential range (−0.66 to −0.95 V vs RHE). Furthermore, it was revealed that the formation of CO and C2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…AEM: anion exchange membrane. Involved catalysts for comparison are including Cu/CuS x , [10c] Cu 2 O/CuS, [33] Cu/Au, [34] S‐modified Cu, [11] thiocyanate‐derived Cu, [35] S‐doped Cu 2 O, [10a] electro‐deposited CuS x , [10b] Cu 2 (CuTCPP) nanosheets, [36] HOD‐Cu, [37] Cu foam, [38] S‐derived Cu, [14] Core/Shell Cu/SnO 2 , [39] CuSn core–shell NPs, [40] Sn SAs on N‐doped graphene, [5d] SnO/C, [5c] Graphene confined Sn quantum sheets, [41] SnO 2 quantum wires, [5b] SnO 2 /Cu 6 Sn 5 /CuO, [42] Pb1Cu SAAs, [7a] Cu–Pd/Mxene, [43] BiNSs‐1, [4a] BiNSs‐2, [44] Bi 2 O 3 @C, [45] Sb SAs/NC, [46] Bi 0.1 Sn, [47] Cu‐Spy, [13] Cu hollow fiber@CNT‐Bi, [48] Sn 0.8 Bi 0.2 @Bi‐SnO x , [49] Cu 2 SnS 3 [50] . For (e, f), brown labels: Cu‐involved catalysts, light green labels: Sn‐ involved catalysts, purple labels: Bi‐ involved catalysts, dark grey label: Pb‐ involved catalyst, black label: Pd‐involved catalyst, and olive label: antimony (Sb)‐involved catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…AEM: anion exchange membrane. Involved catalysts for comparison are including Cu/CuS x , [10c] Cu 2 O/CuS, [33] Cu/Au, [34] S‐modified Cu, [11] thiocyanate‐derived Cu, [35] S‐doped Cu 2 O, [10a] electro‐deposited CuS x , [10b] Cu 2 (CuTCPP) nanosheets, [36] HOD‐Cu, [37] Cu foam, [38] S‐derived Cu, [14] Core/Shell Cu/SnO 2 , [39] CuSn core–shell NPs, [40] Sn SAs on N‐doped graphene, [5d] SnO/C, [5c] Graphene confined Sn quantum sheets, [41] SnO 2 quantum wires, [5b] SnO 2 /Cu 6 Sn 5 /CuO, [42] Pb1Cu SAAs, [7a] Cu–Pd/Mxene, [43] BiNSs‐1, [4a] BiNSs‐2, [44] Bi 2 O 3 @C, [45] Sb SAs/NC, [46] Bi 0.1 Sn, [47] Cu‐Spy, [13] Cu hollow fiber@CNT‐Bi, [48] Sn 0.8 Bi 0.2 @Bi‐SnO x , [49] Cu 2 SnS 3 [50] . For (e, f), brown labels: Cu‐involved catalysts, light green labels: Sn‐ involved catalysts, purple labels: Bi‐ involved catalysts, dark grey label: Pb‐ involved catalyst, black label: Pd‐involved catalyst, and olive label: antimony (Sb)‐involved catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…However, moderate FE HCOO – values ranging from 30.0 ± 8.0% to 62.4 ± 3.4% at −1.2 V RHE were obtained under the same testing conditions (Figures e and S12). These results demonstrate that distinct from other capping ligands, thiocyanate not only activates Cu 2 SnS 3 nanoplates for efficient CO 2 R by displacing OLAM, but also imparts superior formate selectivity likely attributable to electronic effects (see below) …”
mentioning
confidence: 85%
“…These results demonstrate that distinct from other capping ligands, thiocyanate not only activates Cu 2 SnS 3 nanoplates for efficient CO 2 R by displacing OLAM, but also imparts superior formate selectivity likely attributable to electronic effects (see below). 42 The dynamic evolution of catalyst microstructures can dictate CO 2 R activity and selectivity. Previous studies have shown that with copper sulfide-and tin sulfide-based CO 2 R catalysts, metallic Cu or Sn domains and new material interfaces could form during electrolysis and serve as the active sites.…”
mentioning
confidence: 99%
“…[4][5][6] Over the past few years, the two-electron product of formate has proven to be a promising energy commodity for various industrial processes, presenting high values in economic and practical application beneting from high energy density and safe storage. [7][8][9][10] The key is exploring robust and highly active catalysts to accelerate the conversion from the key *OCHO intermediate to formate and inhibit the competition for side reactions.…”
Section: Introductionmentioning
confidence: 99%